The developmental emergence of differential brainstem serotonergic control of the sensory spinal cord - F. Schwaller (Nature Portfolio, 2017)
Abstract Descending connections from brainstem nuclei are known to exert powerful control of spinal nociception and pain behaviours in adult mammals. Here we present evidence that descending serotonergic fibres not only inhibit nociceptive activity, but also facilitate non-noxious tactile activity in the healthy adult rat spinal dorsal horn via activation of spinal 5-HT3 receptors (5-HT3Rs). We further show that this differential serotonergic control in the adult emerges from a non-modality selective system in young rats. Serotonergic fibres exert background 5-HT3R mediated facilitation of both tactile and nociceptive spinal activity in the first three postnatal weeks. Thus, differential descending serotonergic control of spinal touch and pain processing emerges in late postnatal life to allow flexible and context-dependent brain control of somatosensation.